Novel multifunctional colloidal carbohydrate nanofiber electrolytes with excellent conductivity and responses to bone cancer cells. (20th November 2015) - Gökmen, Fatma Özge; Rzayev, Zakir M.O.; Salimi, Kouroush; Bunyatova, Ulviya; Acar, Selim; Salamov, Bahtiyar; Türk, Mustafa
Graphical abstract: Highlights: The multifunctional carbohydrate NFCs were fabricated by green reactive electrospinning. The incorporation of FA (0.5%) essentialy improved morphology and conductivity of NFCs. The effects of temperature, pressure and conduct time on electrical properties were evaluated. The cytotoxic/apoptotic/necrotic analyses were confirmed anticancer activity of FA-NFCs. Reported conductivity and anticancer activity of novel carbohydrate NFCs for the first time. Abstract: This work presents a new approach to fabricating novel polymer nanofiber composites (NFCs) from water solution blends of PVA (hydrolyzed 89%)/ODA–MMT and Na–CMC/ODA–MMT nanocomposites as well as their folic acid (FA) incorporated modifications (NC-3-FA and NC-4-FA) through green electrospinning nanotechnology. The chemical and physical structures and surface morphology of the nanofiber composites were confirmed. Significant improvements in nanofiber morphology and size distribution of the NFC-3-FA and NFC-4-FA nanofibers with lower average means 110 and 113 nm compared with those of NFC-1/NFC-2 nanofibers (270 and 323 nm) were observed. The structural elements of polymer NFCs, particularly loaded partner NC-2, plays an important role in chemical and physical interfacial interactions, phase separation processing and enables the formation of nanofibers with unique morphology and excellent conductivity (NFC-3-FA 3.25 × 10 −9 S/cm and NFC-4-FA 8.33 × 10 −4 S/cm). This is attributed to the higher surface contact areas and multifunctional self-assembled supramacromolecular nanostructures of amorphous colloidal electrolytes. The anticancer activity of FA-containing nanofibers against osteocarcinoma cells were evaluated by cytotoxicity, apoptotic and necrotic analysis methods.